Spatial analysis of rural services in the district of Fallujah, Zgharit village, as a model - المحمدي, عبد الرزاق محمد جبار (Journal of Planner and Development, 2021)
The study of services in villages is one of the imperative matters that must   be focused on, because it leads to increased attention, which reduces the differences between the countryside and the urban. The extent of its.  It is well known that community services need to be reached by a person, unlike the anchor services that reach people, here the population distribution plays an important and prominent role in signing these services, so the dispersed distribution pattern and the gathering pattern appeared in the distribution, thus an effect on the time and distance that the person walked to obtain The services are community-based. Therefore, there appeared an integration in the components of the village, especially the residential and agricultural. The research has been enhanced by field study, especially the questionnaire, which was distributed to a random sample of the population, dependingon the number of the population, ie approximately 110 forms were distributed to include all the communities of the village, and the analysis included the nearest neighbor technique in geographic information systems.components of the village were subjected to sabotage and destruction in the war against ISIS, including shops, a mosque and a school, and they need great financial capabilities. Some services suffer from difficulty accessing them if some of them reach 3 km as in services Health andeducational, in addition to the dispersal of these services, and the researcher recommended compensation for the affected people in an urgent manner, especially the shops, building the destroyed mosque andthe Qatfan school, with changing their locations and making them more effective and attracting the population,Adopting planning standards when establishing any service or use so that it serves the largest number of residents within the village and neighboring villages .